Modelling of Liquid Hydrogen Transfer Operations Through Steady-state Simulations - Lucas M. Claussner; Pramoth Thumattin Sathiamoorthy; Federico Ustolin (Chemical Engineering Transactions)
This study investigates the transfer processes of liquid hydrogen (LH2), a versatile energy carrier widely used in sectors such as space exploration, aviation, land-based mobility, industrial processes, and maritime operations. Despite its potential, the low boiling point and density of LH2 present significant challenges in handling, storage, and transportation, with limited current understanding of the thermodynamics involved in storing and filling cryogenic LH2 tanks. To address this, a static model for LH2 transfer via pipelines was developed using Aspen HYSYS, incorporating key variables such as mass flow rate, pressure, temperature, and pipeline roughness. The simulations explored a range of operating conditions, including mass flow rates (5 to 400 kg/h), inlet pressures (1.5, 6, and 10 bar), and inlet temperatures (19 K, 20 K, and saturation temperatures), as well as pipeline roughness (1.5 mm). The results demonstrate that pipeline roughness and flow rate are critical factors influencing pressure drop and vapor formation, while control valve positioning is essential for optimizing the filling process. This study offers valuable insights into improving the efficiency and safety of LH2 transfer systems, providing practical recommendations for industries reliant on cryogenic technologies. Additionally, optimizing the transfer process could mitigate hydrogen loss through boil-off gas (BOG) venting and reduce the risk of overpressure, preventing the activation of safety devices that could potentially lead to containment breaches. Future research should extend the model to account for inclined pipelines, flexible piping systems, and additional cryogenic components, further enhancing its industrial applicability.